Agricultural growth as a key to poverty alleviation - Brown, Lynn R.; Haddad, Lawrence J. (International Food Policy Research Institute, 1994)
Poverty is a significant and persistent problem in developing countries. Over 1.1 billion people live in households that earn a dollar a day or less per person. Almost half of the population of South Asia and Sub-Saharan Africa lives in absolute poverty; only East Asia has managed to substantially reduce the proportion of its population that is absolutely poor. Agricultural growth stimulates economic growth in nonagricultural sectors, which, in turn, results in increased employment and reduced poverty. This further stimulates demand for agricultural goods, acting as a growth multiplier in the agricultural sector. The limited availability of new land, however, means that agricultural intensification -- increasing the productivity of land already under cultivation--is the key to alleviating poverty through an agricultural growth strategy. Thus addressing rural poverty in the first instance is a crucial catalyst in igniting agriculture as an engine of growth in an economy. The authors conclude with a set of recommendations that, while addressing poverty in its most immediate form, promotes sustained poverty alleviation and economic growth.